2008
DOI: 10.1037/0096-1523.34.4.811
|View full text |Cite
|
Sign up to set email alerts
|

Do all kids look alike? Evidence for an other-age effect in adults.

Abstract: The current study provides evidence for the existence of an other-age effect (OAE), analogous to the well-documented other-race effect. Experiments 1 and 2 demonstrate that adults are better at recognizing adult faces compared with faces of newborns and children. Results from Experiment 3 indicate that the OAE obtained with child faces can be modulated by experience. Moreover, in each of the 3 experiments, differences in the magnitude of the observed face inversion effect for each age class of faces were taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
173
1
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(189 citation statements)
references
References 25 publications
(33 reference statements)
7
173
1
8
Order By: Relevance
“…Since the participant age was closer to those of the adults pictured in the facial stimuli than to those of neonates, adult participants were more adept at categorizing adult faces than infant faces, leading to lower performance with neonate face stimuli. Indeed, adults have been shown to perform better when recognizing adult faces than with faces of different ages, resulting in an other-age effect (Kuefner et al, 2008;Lamont, Stewart-Williams, & Podd, 2005). Finally, by including the output from the GWF model in our analysis, we found that certain spatial Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Since the participant age was closer to those of the adults pictured in the facial stimuli than to those of neonates, adult participants were more adept at categorizing adult faces than infant faces, leading to lower performance with neonate face stimuli. Indeed, adults have been shown to perform better when recognizing adult faces than with faces of different ages, resulting in an other-age effect (Kuefner et al, 2008;Lamont, Stewart-Williams, & Podd, 2005). Finally, by including the output from the GWF model in our analysis, we found that certain spatial Fig.…”
Section: Discussionmentioning
confidence: 78%
“…All were Caucasian, and none had children. The participants were selected prior to testing via a questionnaire to ensure that none had any extensive past exposure to infants' faces (Kuefner, Macchi Cassia, Picozzi, & Bricolo, 2008).…”
Section: Participantsmentioning
confidence: 99%
“…For example, Anastasi and Rhodes (2005) asked children and adults to study photographs of children and adults, and in a subsequent recognition test both adults and children recognized own-age faces more accurately than other-age faces. This own-age bias in face recognition is well established in the literature, and the predominant theoretical accounts of the own-age bias suggest that it reflects more extensive experience with members of the same age group than with other age groups (Hills & Lewis, 2011;Kuefner, Macchi, Picozzi, & Bricolo, 2008).…”
Section: Own-age Biases In Adults' and Children's Joint Attention: Bimentioning
confidence: 96%
“…One reason for floor and ceiling effects potentially is the use of age-inappropriate stimuli. Given that the own-age bias exists in face perception, in which participants show a larger FIE for own-age than other-age faces (Anastasi & Rhodes, 2005;Harrison & Hole, 2009;Hills & Lewis, 2011;Kuefner, Macchi Cassia, Picozzi, & Bricolo, 2008), 5 in order to avoid floor effects, faces should be age-matched to the participants. In adults, the processing of other-group faces has been theoretically linked to not using the most expert configural processing system (Hugenberg & Corneille, 2009;Michel, Rossion, Han, Chung, & Caldara, 2006), which lowers performance in such tasks.…”
Section: Introductionmentioning
confidence: 99%